2022
DOI: 10.1111/aje.13007
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife‐vehicle collisions in Moroccan Atlantic Sahara: Impact on resident species and Afro‐Palearctic birds for conservation purposes

Abstract: In this study, we described the temporal and spatial patterns of wildlife‐vehicle collisions in Dakhla‐Laayoune regions, using counts from cars for two years (2018–2021). A total of 462 roadkills were documented (monthly average of 0.075 roadkills/km), comprising 16 species, including mammals (residents), reptiles (residents), and birds (residents and migrants). Seasonal abundance and diversity of roadkills revealed a high peak during breeding and migration periods for all species. The generalised linear mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 118 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…Human-made elements in the airspace have become an increasingly common barrier to migratory movements, and birds collide with anthropogenic structures throughout the world's migration systems (Marques et al 2014, Santiago-Alarcon and Delgado-V 2017 Hager et al 2017, Bernardino et al 2018, Pinto et al 2020, Uddin et al 2021, Mansouri et al 2022). Not all collisions result in observed mortality: only a small percentage (approximately 6–7%) of collisions at residential buildings are estimated to be immediately fatal (Kummer and Bayne 2015, Samuels et al 2022), but the long-term survival probability remains largely unknown (Klem 1990).…”
Section: Anthropogenic Threat Typesmentioning
confidence: 99%
“…Human-made elements in the airspace have become an increasingly common barrier to migratory movements, and birds collide with anthropogenic structures throughout the world's migration systems (Marques et al 2014, Santiago-Alarcon and Delgado-V 2017 Hager et al 2017, Bernardino et al 2018, Pinto et al 2020, Uddin et al 2021, Mansouri et al 2022). Not all collisions result in observed mortality: only a small percentage (approximately 6–7%) of collisions at residential buildings are estimated to be immediately fatal (Kummer and Bayne 2015, Samuels et al 2022), but the long-term survival probability remains largely unknown (Klem 1990).…”
Section: Anthropogenic Threat Typesmentioning
confidence: 99%
“…In recent years human developmental and encroachments activities are risk for wildlife habitat because these activities fragmenting their habitat and isolating local animals beyond the loss of animals on road vehicles are also damaging plants by polluting them [7]. The major groups of animals killed by vehicles are reptiles, amphibians, mammals and small animals including birds [8], Collision of animals with trains are also common [9].Roads affect the population of wild animals and are source of barrier between animal's leads to reduction of biodiversity results in population isolation [10]. To save wild life it is necessary to made bridges at regular distance for animal's crossings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the risk of animal‐vehicle collisions may vary considerably along the year and depends on whether the species has resident populations (Kantola et al, 2019). Nevertheless, different studies have demonstrated that migratory birds are highly killed on roads (Lala et al, 2021; Mansouri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%